The effects of topical melatonin on oxidative stress, apoptosis signals, and p53 protein expression during cutaneous wound healing - (:unkn) unknown (My University, 2015)
0

Elimination of reactive oxygen species (ROS) can be an important strategy to improve healing of wounds. ROS have an effect on proliferation and cell survival signaling, which results in alteration of apoptotic pathways in cells. Melatonin has antioxidant properties on skin wounds. In our study, we investigated the effects of topical melatonin (3%, w/w) on apoptosis and p53 protein expression together with parameters of oxidative stress in a cutaneous excision wound model. Bcl-2 protein levels in wound tissue at the end of days 3, 7, and 14 were significantly increased, while caspase-3 activity and p53 protein expression in wound tissue at the end of days 3, 7, and 14 were also reduced with melatonin treatment during wound healing. On days 3 and 7 after the wound, malondialdehyde level was reduced and glutathione was increased with melatonin treatment. Melatonin decreased myeloperoxidase levels and increased hydroxyproline levels in wound tissue at the end of day 7. However, melatonin had no significant effect on percentage of wound closure. Considering our results, topical melatonin displays antioxidant, antiapoptotic, and p53-inhibitory effects, but these effects are not sufficient for the acceleration of wound closure.
Keywords: Biyoloji